Espécies do complexo Fusarium solani (FSSC) associadas a doenças radiculares da soja - Sousa, Thamires Yslanny Oliveira (2020)
Soybeans are planted in most of the parts of the Brazilian territory. Productivity can be affected by biotic or abiotic factors. Amongst biotic factors, fungal diseases like red root rod and sudden death syndrom SDS are the most important, caused by members of the Fusarium solani species complex FSSC. Most common symptoms are root rot and typical foliar necroses, like mottling and interveinal chlorosis. This chlorosis is induced through phytotoxins, produced by the pathogen. The objective of this study was to evaluate, which species of the FSSC are associated with those symptoms in soybean plantations in Brazil. A collection of 17 isolates was obtained from symptomatic plants from the states of Minas Gerais, Goiás, Mato Grosso and Mato Grosso do Sul. After preparation of monospore cultures, morphological markers of the isolates were evaluated. Mating types were determined by means of a specific PCR reaction and lab crosses were then conducted to determine biological species. Representative isolates of each morphotype were used in pathogenicity tests by inoculation of plantlets by the method of infested sorghum grains. Isolates were identified as belonging to three species of the FSSC, F. tucumaniae and F. crassistipitatum, from Clade 2, and F. paranaense, from Clade 3. After crossing isolates of opposite mating types, isolates of F. tucumaniae induced fertile perithecia, exsudating viable ascospores. All tested isolates induced variable symptoms, but also typical symptoms of SDS. Fusarium tucumaniae induced mottling and interveinal chlorosis 30 days after inoculation, and necroses of leaves 40 days after inoculation. Fusarium crassistipitatum and F. paranaense didn’t induce foliar symptoms. Nevertheless, all species tested induced typical symptoms of red root rot. This study confirms F. tucumaniae as the causal agent of SDS in Brazil. The results presented here contribute not only to the better understanding of members of the FSSC, which can cause PVR and SDS in soybean plantations in Brazil, but also to the development of strategies for integrated disease management, mainly regarding the selection of plant material, resistant to those pathogens.